Comparison of the Quality of Enzymatically Treated Soursop Juice and Jackfruit Juice - REVINCHANDER, KESAVARHNI; Mohamad Fuzi, Siti Fatimah Zaharah (Enhanced Knowledge in Sciences and Technology, 2022)
The quality of soursop juice and jackfruit juice with different ratios of enzyme mixture were investigated in terms of maximum clarity, juice yield and viscosity. Three mixture of enzyme ratios were obtained from the maceration of pectinase (0.5 - 1.5 %v/w) and cellulase (0.5 – 1.5%v/w) for each fruit juices. The clarity of the both fruit juices were analyzed by spectrometric method.  Extraction yield and viscosity of enzymatically treated juices were measured. The absorbance and viscosity of both fruit juices significantly decrease, in jackfruit juice the absorbance (0.846 – 0.167) and viscosity (0.202 Pa.s – 0.020 Pa.s) when 0.5:1.5 (pectinase:cellulase) enzyme mixture used while in soursop juice the absorbance (0.667 - 0.087) and viscosity (0.163 Pa.s - 0.031 Pa.s) when 1.0:1.0 (pectinase:cellulase) enzyme mixture used. The juice yield extraction increased significantly in both fruit juices when using 0.5:1.5 (pectinase:cellulase), in jackfruit juice rises up to 83% while soursop juice rises up to 65%. For the jackfruit juice, it was found that 0.5:1.5 (pectinase:cellulase) enzyme mixture tend to produce more qualified juice while for the soursop juice enzyme mixture of 1.0:1.0 (pectinase:celluase) shows more qualified juice respectively. This research proves that the quality of the jackfruit juice and soursop juice tend to increase when they are enzymatically treated by using enzyme mixture in the aspect of clarity, juice yield, and viscosity compared to untreated samples.